Representation of Radicalism in Local Media - Dulwahab, Encep; Muhtadi, Asep Saeful (International Journal of Media and Communication Research, 2025)
The media has a special fascination with radicalism. Even though it is an old issue, radicalism is always a topic of coverage that is never overlooked by the media. This is no exception to the local media located in Bandung, Yogyakarta, and Bali, which have the characteristics of each region, and there is always radicalism, which leads to conflict. By using critical discourse analysis methods, this research aims to find out how local media represents radicalism. The results of the research found that the local media considers that the issue of radicalism is an issue that is embedded in the media; where there are activities or issues related to radicalism, it must be spread because of the dangerous effects of radicalism. Local media, in representing radicalism, reinforces the discourse that this radicalism is a dangerous, forbidden, and difficult to eradicate ideology. Local media also represents that this understanding of radicalism is an understanding that intensively and systematically seeks to spread understandings to various groups, with various strategies and media used massively. Local media shows that this radicalism has been developing in Indonesia for a long time and is difficult to eradicate. Its existence often haunts society and the government. There is a slight difference in the way it is represented, Tribun Bali represents radicalism inserted in news with other themes. Tribun Bali in its reporting about radicalism was not direct. Meanwhile, Tribun Yogyakarta and Ayobandung.com immediately reported on the issue of radicalism. Differences in local media in representing radicalism are due to differences in each media's interpretation of facts.